Crafting the Change: The Role of Employee Job Crafting Behaviors for Successful Organizational Change - Petrou, Paraskevas; Demerouti, Evangelia; Schaufeli, Wilmar B. (Journal of Management, 2018)
Organizations today have to change constantly. Although both practitioners and scientists agree that organizational change communication is the most effective strategy to improve employee adjustment to change, little is known about how change communication enhances more proactive employee reactions to change. The present study addresses employee job crafting behaviors (i.e., seeking job resources, seeking job challenges, and reducing job demands) as a tool used by employees in order to respond to and cope with implemented organizational change. Using regulatory focus theory, we propose that on the basis of their promotion or prevention regulatory focus, employees respond to organizational change communication via job crafting behaviors that further enhance or hinder their adjustment to change (i.e., work engagement and adaptivity). Hypotheses are tested with a latent change score analytical approach via a three-wave longitudinal design among 368 police officers. Findings reveal that while adequate change communication is linked to increased job crafting behaviors for promotion focused employees, inadequate change communication is linked to increased job crafting behaviors for prevention focused employees. Furthermore, seeking resources is positively associated with employee work engagement, seeking challenges is positively associated with adaptivity, and reducing demands is negatively associated with work engagement. These findings bring together three different streams of literature (i.e., organizational change, regulatory focus, and job crafting). Implications for management are outlined, and they are, thereafter, translated to a specific workplace intervention, which is proposed to organizations and managers.